2015
DOI: 10.7567/apex.8.083005
|View full text |Cite
|
Sign up to set email alerts
|

Spin-torque-induced oscillation at zero bias field in a magnetoresistive nanopillar with a free layer with first- and second-order uniaxial anisotropy

Abstract: Spin-torque-induced magnetization dynamics in a nanopillar having a perpendicularly magnetized free layer with firstand second-order uniaxial anisotropy and an in-plane magnetized reference layer is studied theoretically on the basis of the macrospin model. It is shown that in the presence of second-order uniaxial anisotropy, self-oscillation is induced even at zero bias magnetic field. Analytical expressions for the threshold current, condition of the second-order anisotropy constant required for oscillation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, STT-based spin dynamics also offer the possibility of important new developments in nanooscillators. This has resulted in the emergence of the field of STT-based nano-oscillators as an active area in spintronics research [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, STT-based spin dynamics also offer the possibility of important new developments in nanooscillators. This has resulted in the emergence of the field of STT-based nano-oscillators as an active area in spintronics research [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The geometric confinement of the spin waves in nanowires suppresses some nonlinear scattering channels such as four-magnon scattering 34 35 , which turns out to be sufficient for the excitation of sustainable self-oscillations over micrometer-scale regions of the nanowire 11 . In spite of the large excitation volume and the associated diminished impact of the random thermal torques on the magnetization dynamics, the spectral linewidth of the microwave signal generated by nanowire STOs was found to be comparable to that of nanoscale STOs 22 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 . This result can be attributed to the simultaneous excitation of several SW modes in nanowire auto-oscillators, because it is known that the interactions between the simultaneously excited self-oscillatory modes can substantially increase the linewidths of the generated modes 51 52 .…”
mentioning
confidence: 95%
“…where θ is the polar angle of magnetization unit vector, and K 1 and K 2 are the firstand the second-order MA coefficients, respectively. Recent experimental [15][16][17][18][19][20] and theoretical [21][22][23][24][25][26] studies revealed the important properties of K 19) In this paper, we calculate K 1 and K 2 of Fe atomic monolayers (MLs) on the MgO(001) substrate under electric fields by using first-principles calculations based on fullrelativistic self-consistent calculations. The dependence of the thickness of the Fe layer on K 1 and K 2 was studied by varying the number of Fe MLs from one to four.…”
mentioning
confidence: 99%